Evolutionary Equations with Applications in Natural Sciences - Banasiak, Jacek (Lecture notes in mathematics, 2015)
Wilson Lamb: Applying functional analytic techniques to evolution equations -- Adam Bobrowski: Boundary conditions in evolutionary equations in biology.-Ernesto Estrada: Introduction to Complex Networks: Structure and Dynamics.-Jacek Banasiak: Kinetic models in natural sciences -- Philippe Laurençot: Weak compactness techniques and coagulation equations -- Ryszard Rudnicki: Stochastic operators and semigroups and their applications in physics and biology -- Mustapha Mokhtar-Kharroubi: Spectral theory for neutron transport.-Anna Marciniak-Czochra: Reaction-diffusion-ODE models of pattern formation -- Mapundi Kondwani Banda: Nonlinear Hyperbolic Systems of Conservation Laws and Related Applications